2013
DOI: 10.1080/00401706.2013.765316
|View full text |Cite
|
Sign up to set email alerts
|

A Hierarchical Model for Aggregated Functional Data

Abstract: In many areas of science one aims to estimate latent sub-population mean curves based only on observations of aggregated population curves. By aggregated curves we mean linear combination of functional data that cannot be observed individually. We assume that several aggregated curves with linear independent coefficients are available. More specifically, we assume each aggregated curve is an independent partial realization of a Gaussian process with mean modeled through a weighted linear combination of the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Special attention has been devoted to the functional data analysis. A hierarchical model for aggregated functional data is introduced by Dias et al , with an application to the distribution of energy among different types of consumers. Other fashionable techniques often used are neural networks and the Gaussian process .…”
Section: A Review Of Alternative Modelsmentioning
confidence: 99%
“…Special attention has been devoted to the functional data analysis. A hierarchical model for aggregated functional data is introduced by Dias et al , with an application to the distribution of energy among different types of consumers. Other fashionable techniques often used are neural networks and the Gaussian process .…”
Section: A Review Of Alternative Modelsmentioning
confidence: 99%
“…The estimation of typical load curves of electrical consumption using aggregated functional data was first done by Dias, Garcia, and Martarelli () and revisited in the Bayesian framework by Dias, Garcia, and Schmidt (). However, these authors assumed that the reported classes were equal to the true classes.…”
Section: Introductionmentioning
confidence: 99%
“…However, the high dimensionality of the problem and the fact that there is no replication of the data results in poor aggregated covariance estimates, with sample covariance matrices having high condition numbers and therefore often being numerically singular. To overcome this problem, we model the covariance function as suggested by Dias et al (2012), we assumed that the covariance of each ǫ i (t) in model (2.4) is homogeneous and given by…”
Section: Artificial Datasetsmentioning
confidence: 99%
“…This is an interesting sample to analyze since it was designed to achieve an orthogonal design in the calibration step. It was also analyzed, using a Bayesian perspective, but only for the calibration step, by Dias, Garcia and Schmidt (2012). The other one is the so-called Tecator Data which is used by several authors to compare the techniques in terms of prediction tool, for example in the works by Borggaard and Thodberg (1992), Eilers, Li andMarx (2009), Ferraty and, Aneiros-Pérez and Vieu (2006).…”
Section: Introductionmentioning
confidence: 99%